CITRA KUASA PEREMPUAN JAWA DALAM NOVEL PEREMPUAN JOGJA DAN MARUTI, JERIT HATI SEORANG PENARI KARYA ACHMAD MUNIF - Rahmawati, Dian (ATAVISME, 2007)
Javanese women who considered as a give in. surrender, and nrimo, oftently stereotyped as a complementary for their man, which known as konco wingking, with the famous principle of live swarga nunut, neraka katut (they came with their husband, no matter where he goes). Women also considered as a seducer (while in the fact that men have same potential to them) and violence ofently comes because their attitude and nature. Sociologically. definition of power was someone ability to influencing other's attitude, behaviour. and way of life. According to the definition, Javanese women have a big power to change something bad to the good one, not only for themselves. hut for everybody. This research used literature sociology to see that literature was reflective of society and deconstruction method to deconstruct standard society understanding that women were a second-class citizen that has in equivalent rights to the men. By the novel, we can figure out about the image of Javanese-women power to themselves. their family, and to the society.